Effectiveness of Pictorial Health Warnings on Tobacco Products in Creating Awareness among 15-17 Years Old School Children in Lucknow - Sarvesh Bansal; Shitanshu Malhotra; Madhusudan Krishna; Shikha Chaudhary; Gunjan Agarwal (Indian Journal of Forensic Medicine & Toxicology, 2021)
Aim: The present study was planned to assess the effectiveness of pictorial health warnings on tobaccoproducts in creating awareness among 15-17 years old school children in Lucknow.Materials and method: The present cross sectional study was conducted among 360 students studyingin rural schools of Lucknow. Information about schools was obtained from DEO’s. Sampling was doneusing multistage sampling technique. A specially designed questionnaire was administered to assess theeffectiveness of pictorial health warnings on tobacco products in creating awareness given on the reversepanel of smoked and smokeless tobacco. Statistical analysis was done using chi square and test.Results: The mean knowledge score among male and female was 6.37±1.56 and 6.50±1.73 respectivelywith statistically insignificant difference. Average and poor impact was reported among 21.11%, 1.94% and14.17%, 0.28% of the boys and girls respectively. When different attitude grading was compared statisticallyamong boys and girls, it was found to be statistically significant.Conclusion: The present study threw light on some of the aspects of the young students towards the PictorialHealth Warnings on tobacco packs. The finding also highlights to improve the quality of the PictorialWarnings and make them more robust and impactful